A Case of a Simple Solitary Renal Cyst in a Shih Tzu - Gülersoy, Erdem; Uzunlu, Elgin Orçum; Erol, Büşra Burcu (Veterinarski Glasnik, 2022)
In this report, a clinical case of a solitary renal cyst in a Shih Tzu dog is described. On the basis of clinical and laboratory examinations, and ultrasonographic and radiologic visualizations, provisional and differential diagnoses were made. The Shih Tzu dog described in this report was referred to the Small Animal Hospital of the Faculty of Veterinary Medicine, Selçuk University, for further work-up after a one-week treatment in a private veterinary clinic. In our hospital, a simple solitary renal cyst was detected and was treated successfully with ultrasound-guided percutaneous drainage. The dog was followed-up during two months’ post procedure with renal ultrasonography and four months by phone calls with the owner. The initial complaints such as anorexia and lethargy disappeared after the treatment. The ultrasonographic appearance of the cyst changed from an ovoid anechoic structure into a vague, slightly hyperechoic scar lesion.